The vascular-cambium-specific transcription factor PtrSCZ1 and its homologue regulate cambium activity and affect xylem development in Populus trichocarpa - Sun, Yi; Jiang, Jianing; Zhang, Qiongyue; Zhao, Jinfeng; Ma, Hongyan; Li, Danning; Li, Shuang; Zhou, Chenguang; Li, Wei (Frontiers in Plant Science, 2025)
IntroductionVascular cambium proliferates and differentiates into the secondary xylem (wood), enabling the perennial increase in stem diameter for wood formation. In our previous study, we identified 95 vascular-cambium-specific (VCS) transcription factors (TFs) in Populus trichocarpa.MethodsIn this study, we characterized the function of the highly vascular cambium-expressed heat shock TF among these VCSs, PtrSCZ1, using PtrSCZ1-overexpressing transgenic lines and gene-edited mutants in P. trichocarpa.ResultsOverexpressing PtrSCZ1 or its homolog PtrSCZ3 (OE-PtrSCZ1, OE-PtrSCZ3) led to enhanced cambium activity, increased stem diameter, and a larger xylem proportion. CRISPR-based mutants of PtrSCZ1 and PtrSCZ3 exhibited phenotypes opposite to the OE-PtrSCZ1 and OE-PtrSCZ3 plants. This suggests that PtrSCZ1 and PtrSCZ3 redundantly promote cambium activity and secondary growth, leading to increased radial growth in P. trichocarpa. Overexpression and knockout of PtrSCZ1 and PtrSCZ3 significantly affected the expression of key regulatory factors of cambium (PtrWOX4a, PtrWOX4b, PtrWOX13a, PtrPXYa, PtrVCM1, and PtrVCM2) and disrupted cell wall-related gene expression. This demonstrates that PtrSCZ1 and PtrSCZ3 may function in cambium division activity by regulating these key cambium-associated transcription factors for wood formation.DiscussionOur work identifies PtrSCZ1 and PtrSCZ3 as promising target genes for enhancing wood yield through molecular breeding, and illustrates the role of vascular cambium systems in understanding lateral meristem development.